The Influence of Middle School Teacher Leadership and Students’ Interests on Learning Achievement - Julinda Siregar; Erni Murniarti; Hotmaulina Sihotang; Rosnawati Rosnawati (STAI Hubbulwathan Duri, 2022)
This study aims to determine the influence of teacher leadership and students’ interest in social studies learning achievement. The study used a survey method with correlational techniques. The population of this study were students from three schools in Bogor City, totalling 604 students. The sample in this study was 60 students which were randomly selected. The data were obtained by delivering a questionnaire and analyzed by descriptive statistics. The results of the research conclude that there is a significant effect of the teacher leadership variable on the social studies learning achievement variable for private middle school students in the city of Bogor. It is proven that the value of Sig = 0.00 0.05, t-test = 3.905. Moreover, there is an influence of learning interest in learning on Social Studies on the students’ learning achievement. There is a value of Sig = 0.00 0.05, t-test = 4.904. Furthermore, there is a significant influence on the independent variables of teacher leadership and interest in learning together on the social studies learning achievement of students. This is evidenced by the value of Sig = 0.011 0.05 and F-test = 23.062. These findings conclude that the teacher must perform a good model to increase students’ interests in learning that can provide positive impacts on their learning achievement.